Student Responses in Biology Physics Courses Use Worksheets Based on Scientific Literacy - Dewi Dewantara; Saiyidah Mahtari; M. Misbah; Surya Haryandi (IKIP Mataram, 2019)
This article evaluates student responses in biology physics courses use worksheets based on scientific literacy. Student worksheets are seen as a product developed, and one of the aspects reviewed is the practicality in the context of the implementation of the worksheets in the classroom. Student responses will illustrate how practicality of the learning tool, namely the student worksheet used. The student responses were mined from the questionnaire, which featured the grade of very good, good, enough, poor, and not good. The responses were given by 30 students who took the Biology Physics course from the Physics Education Study Program at Lambung Mangkurat University. Results show that the Student Worksheet is very good for improving scientific literacy in Biology Physics courses and are suggested for widespread implementations, also for another courses.